Exploring the role of international R&D activities in the impact of technological and marketing capabilities on SMEs’ performance - Davcik, Nebojsa S; Cardinali, Silvio; Sharma, Piyush; Cedrola, Elena (Elsevier, 2020)
One of the main challenges for small and medium enterprises (SMEs) is how to leverage their R&D activities in the international markets but current literature offers mixed evidence and inconclusive models in this regard. This paper addresses this gap by exploring the role of international R&D activities in the impact of SMEs’ technological and marketing capabilities on their performance. The authors use in-depth interviews with five Italian SMEs recognized as particularly innovative firms in their own sectors (retail intelligence, business training, shoes, food, and sportswear) to identify the factors driving the success and performance of their international R&D efforts. Findings show that SMEs’ technological and marketing capabilities have dominant and positive effects on their performance in the international markets. Besides extending the literature on the internationalization of R&D by SMEs, these findings highlight the major challenges and opportunities for the managers of internationally active SMEs.